Towards Improving The French’s Teaching By Mathematical Logic in The High School Second Class in Madagascar - Rakotomalala, Hery Frédéric; Razafindrabehita, Lwanga Albert; Ravelomanana, Juvenile Christalin; Ravelojaona, Vatosoa Tsirinala Fabiola; Totohasina, André (Journal of Natural Language and Linguistics, 2026)
This study proposes a pedagogical innovation aimed at introducing formal logic, traditionally applied in mathematics, into the French course in the second class of high school in Madagascar. Conducted in a secondary school in Mahajanga, this research examines the effects of this approach on students’ reasoning abilities and linguistic comprehension skills. Through classroom experimentation and Implicative Statistical Analysis (ISA) using the Implicative and Cohesive Hierarchical Classification based on MGK) (ICHC-MGK) tool, students were exposed to logical concepts such as implication, equivalence, and the logical connectors AND, OR (inclusive/exclusive) within French language modules. The students’ performance indicated that this integration strengthened their reasoning skills, particularly among those with a strong linguistic foundation. However, some students continued to struggle with complex logical concepts, highlighting diverse pedagogical needs. This study thus demonstrates the interdependence between a non-linguistic discipline (mathematics) and a linguistic discipline (French). This approach has the potential to enhance the Malagasy secondary education system by fostering logical reasoning as a tool for learning French as a language of instruction. It also advocates for policymakers to implement this method in other secondary schools across Madagascar and invest in teacher training, thereby equipping students with the interdisciplinary reasoning skills essential for their future.